The effects of Aspartame on the postnatal development of the cerebellum in male albino rat offspring - Omyma Zeanelabdeen Fakhry*; Dorreia AbdAllah Mohamed; Maha Abdelbaki Ahmed (SVU - International Journal of Medical Sciences, 2022)
Background: Aspartame (ASP) is a non-nutritive sweetener that is greatly used in drinks, foods, beverages and pharmaceuticals. There are controversies about its safety. So, studies are important to prove or disapprove the present fears about aspartame. Objectives: It is to evaluate the effect of ASP on the postnatal development of cerebellum in rat offspring. Material and Methods: Eight male offspring of each control and experimental groups were randomly selected at the postnatal day (PND): 1,7,15.21 and 60 days. Aspartame (250 mg/kg body weight/day) was given orally to experimental group of animals during pregnancy and lactation period. Specimens were prepared for light and electron microscopic studies. Morphometric and statistical studies were done to measure the diameter of granular cells nuclei. Results: Control group of animals showed normal development of cerebellar cortex. Cerebella of the experimental group of animals showed a disrupted architecture with degenerative changes especially in Purkinje cells. Splitting and disruption of the myelin sheath were detected. Experimental group showed a highly significant decrease in the mean granular cell nuclear diameter (p < 0.001) when compared to the control group. Conclusions: Administration of aspartame during pregnancy has harmful effects on the developing cerebellum of albino rat’s offspring.